Pengaruh Kualitas Pelayanan Terhadap Kepuasan Peserta Bpjs Kesehatan Kc Magelang - Siti Nur Faizah; Jihad Lukis Panjawa (Jurusan Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis, Universitas Lampung, 2020)
Service delivery carried out by service personnel must refer to the main objective of service, namely customer satisfaction. This research analyzes the effect of service quality on the satisfaction of BPJS Kesehatan KC. Using quantitative research methods and primary data using sampling techniques using the Slovin formula using 100 respondents from a total of 1027437 BPJS Kesehatan participants. By using variables tangible, reliability, responsiveness, assurance, and empathy are used to measure the satisfaction of participant services. The results of this study R square (coefficient of determination) obtained R Square value of 0.788 (78.8%), which means 78.8% of service satisfaction variables are influenced by tangible variables, reliability, responsiveness, empathy, and assurance and the remaining other variables outside the research variables. There is a partially significant effect consisting of the variable reliability, empathy, and assurance that affect service satisfaction. While variables tangible and responsiveness do not affect customer satisfaction. BPJS Kesehatan KC Magelang must pay more attention and improve service quality factors, namely tangible and responsiveness so as to provide service satisfaction for participants.